2013
DOI: 10.1155/2013/815325
|View full text |Cite
|
Sign up to set email alerts
|

Waldenström Macroglobulinemia: Clinical and Immunological Aspects, Natural History, Cell of Origin, and Emerging Mouse Models

Abstract: Waldenström macroglobulinemia (WM) is a rare and currently incurable neoplasm of IgM-expressing B-lymphocytes that is characterized by the occurrence of a monoclonal IgM (mIgM) paraprotein in blood serum and the infiltration of the hematopoietic bone marrow with malignant lymphoplasmacytic cells. The symptoms of patients with WM can be attributed to the extent and tissue sites of tumor cell infiltration and the magnitude and immunological specificity of the paraprotein. WM presents fascinating clues on neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 253 publications
(265 reference statements)
1
14
0
Order By: Relevance
“…The latter represent the B-cell population from where most cases of WM are thought to be derived. 18,19 Methods…”
Section: Introductionmentioning
confidence: 99%
“…The latter represent the B-cell population from where most cases of WM are thought to be derived. 18,19 Methods…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Ghobrial et al with 26 treatment-naïve WM patients, 6 cycles of bortezomib combined with rituximab showed ORR 100%, 1-year PFS and OS rates of 75% and 96%, respectively 39 . RCyD combination showed a median PFS of 35 months and 5-year OS rate of 62% 28,31 . Similar to RCyD, bortezomib, dexamethasone, and rituximab (BDR) combination in two studies showed ORR 90–96%, PFS rate 40–80%, and OS rate 80–100% with significant improvement in BM involvement and serum IgM levels 40,41 .…”
Section: Managementsmentioning
confidence: 98%
“…Also, careful interpretation is needed to differentiate IgM flare from lack of response or disease progression. Plasmapheresis is suggested in patients with high IgM (>4000mg/dL) or hyperviscosity symptoms to prevent IgM flare 28 . Of note, late intolerance to rituximab occurs in 10–15% of cases.…”
Section: Managementsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Further therapeutic advances and the closure of pathophysiological knowledge gaps may depend in no small measure on the development of an accurate, genetically engineered mouse model (GEMM) of human IgM + LPL in which WM-like neoplasms develop predictably with short latency and high tumor incidence. 11 …”
Section: Introductionmentioning
confidence: 99%